Shallot (Allium ascalonicum): An overview of antidiabetic activity by α-glucosidase inhibition - Ramadaini, Tiara; Sumiwi, Sri Adi; Febrina, Ellin (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Allium ascalonicum (shallot) is a medicinal plant with promising potential in the management of type 2 diabetes mellitus (T2DM). This review summarizes the phytochemical constituents, mechanisms of action, and existing research gaps that warrant further exploration for targeted drug development. A systematic literature search was performed using PubMed, ScienceDirect, and Google Scholar to identify relevant studies published between 2013 and 2023. Only full-text original research articles in English were included, while reviews and incomplete studies were excluded. The search strategy employed the keywords: “Allium ascalonicum OR shallot AND α-glucosidase.” The findings indicate that A. ascalonicum demonstrates significant antidiabetic activity across in vitro, in vivo, and limited human studies, primarily through inhibition of the α-glucosidase enzyme. This activity is largely attributed to quercetin and other flavonoid compounds, which play an essential role in reducing blood glucose levels and mitigating oxidative stress. Collectively, the evidence highlights the therapeutic potential of A. ascalonicum as a natural α-glucosidase inhibitor. However, further clinical investigations and comprehensive toxicity assessments are required to establish its efficacy and safety as a standardized herbal medicine and future phytopharmaceutical candidate for diabetes management.